NSUN2 lactylation drives cancer cell resistance to ferroptosis through enhancing GCLC-dependent glutathione synthesis - Kaifeng Niu; Zixiang Chen; Mengge Li; Guannan Ma; Yuchun Deng; Ji Zhang; Di Wei; Jiaqi Wang; Yongliang Zhao (Redox Biology)
Lactate-mediated lactylation on target proteins is recently identified as the novel posttranslational modification with profound biological functions. RNA 5-methylcytosine (m5C) modification possesses dynamic and reversible nature, suggesting that activity of its methyltransferase NSUN2 is actively regulated. However, how NSUN2 activity is response to acidic condition in tumor microenvironment and then regulates cancer cell survival remain to be clarified. Here, we demonstrate that NSUN2 activity is enhanced by lactate-mediated lactylation at lysine 508, which then targets glutamate-cysteine ligase catalytic subunit (GCLC) mRNA to facilitates GCLC m5C formation and mRNA stabilization. The activated GCLC induces higher level of intracellular GSH accompanied by decreased lipid peroxidation and resistant phenotype to ferroptosis induction by doxorubicin (Dox) in gastric cancer cells. Specifically, the effect of NSUN2 lactylation-GCLC-GSH pathway is nearly lost when NSUN2 K508R or GCLC C-A mutant (five cytosine sites) was introduced into the cancer cells. We further identify the catalytic subunit N-α-acetyltransferase 10 (NAA10) as the lactytransferase of NSUN2, and lactate treatment substantially enhances their association and consequent NSUN2 activation. Taken together, our findings convincingly elucidate the signaling axis of NAA10-NSUN2-GCLC that potently antagonizes the ferroptosis under acidic condition, and therefore, targeting NSUN2 lactylation might be an effective strategy in improving the prognosis of cancer patients.